Hand grip strength in elderly participants in community groups - Belmonte, Luana Meneghini (2014)
Objective: To analyze the hand grip strength (HGS) in elderly participants in community groups and its relation to gender, physical activity practice, diabetes, systemic arterial hypertension and osteoporosis. Methods: This is a descriptive, cross-sectional study with a quantitative approach, performed with 79 elderly people of both genders, participants of community groups in the city of Palhoça-SC. Clinical data and HGS were assessed from July to October 2012, being analyzed the influence of the variables on the HGS. Results: The sample comprised 69 women (87.3%) and 10 men (12.7%), where 34.2% (n= 27) of the elderly reported having diabetes, 55.7% (n= 44) systemic arterial hypertension and 25.3% (n= 20) osteoporosis. The men’s HGS (63.97 ± 15.17 pounds) was higher than the women’s (40.52 ± 12.27 pounds), (p=0.001). There was no significant difference between the HGS averages among the elderly practitioners of physical activity and the non-practitioners (p= 0.99). There was influence of osteoporosis on the HGS, where the elderly without the disease presented more strength than the affected ones (p=0.002). Conclusion: The elderly showed lower HGS values than expected for their age, being men’s HGS higher than the women’s. The physical activity practice, systemic arterial hypertension and diabetes did not influence the HGS, however, the elderly with osteoporosis showed diminished HGS. doi:10.5020/18061230.2014.p85